PENGARUH LINGKUNGAN KERJA, MOTIVASI, KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI JOB SATISFACTION PADA KARYAWAN PT BPR BKK TAMAN PERSERODA PEMALANG: Dibuat Oleh Indah Prima Lestari, Djauhar Edi Purnomo, R Irawan S - supriyatno, irawan; edi, djauhar; prima, indah (Neraca, 2021)
This research was carried out to determine the effect of work environment, motivastion and compensation on performance through job satisfaction as an intervening variable PT BPR BKK TAMAN Perseroda, This study used porposive sampling technique where the selected sample was 50 respondents who were employees of PT BPR BKK TAMAN Perseroda, a financial services provider company, the date were analyzed throught Structural Equation Modeling (SEM), method and SMARTPLS 3 dfe to the small number of targeted respondent from result of the study, it was found that the environment, motivation, and compensation had a significant effect on job satisfaction and employee performance, beside job satisfaction had a significant effect on performance moreover the intervening varable namely job satisfaction could partially moderate exogenous variable Keyword: work environment, work motivation, compensation, performance, job satisfaction